A transgender girl's experience: sexual exploitation and systems involvement. Issue 2 (15th March 2020) - Hammond, Ivy; Godoy, Sarah; Kelly, Mikaela; Bath, Eraka
Abstract : Purpose: The available research on specialized interventions for youth experiencing commercial sexual exploitation almost exclusively focuses on the impact and efficacy related to cisgender girls, despite the inclusion of youth who identify as transgender in these programs. This paper aims to present a case study on the experience of a transgender adolescent girl who experienced commercial sexual exploitation and provides a narrative of the multifarious challenges she faced while involved in institutional systems of care. Design/methodology/approach: This paper conducted an in-depth case review of all records on "Jade, " a white adolescent transgender girl who experienced commercial sexual exploitation, from a specialty court program in the juvenile justice system between 2012 and 2016. Her experiences throughout childhood exemplify many of the unique challenges that transgender girls and young women with histories of exploitation or trafficking may encounter within service delivery and socioecological systems. This paper applied concepts adapted from the gender minority stress theoretical model to understand how minority gender identity can shape the experiences and outcomes of the youth impacted by commercial sexual exploitation. Findings: Jade's narrative underscores the interplay of gender-based sexual violence, heteronormative structural barriers, transphobia and their intersectional impact on her experience while receiving specialized care. The intersectional hardships she experienced likely contributed to adverse biopsychosocial outcomes, including high rates of medical and behavioral health diagnoses and expectations of further rejection. Originality/value: This paper highlights the extraordinary challenges and barriers faced by an often under-recognized and overlooked subset of the youth impacted by commercial sexual exploitation, who may receive services that do not account for their unique needs related to gender expression and identity. This paper exemplifies how internalized stigma along with expectations of further rejection and victimization have implications for clinical and multidisciplinary intervention settings. Jade's case underscores the need for improved access to supportive services for youth with minority gender identities, including peer community-building opportunities. Finally, this paper identifies a critical gap in US legislation and social policy. This gap contributes to the structural harms faced by transgender and gender-nonconforming youth receiving services during or following experiences of commercial sexual exploitation.